Genetic diversity, distribution and domestication history of the neglected GGAtAt genepool of wheat - Ekaterina D. Badaeva; Fedor A. Konovalov; Helmut Knüpffer; Agostino Fricano; Alevtina S. Ruban; Zakaria Kehel; Svyatoslav A. Zoshchuk; Sergei A. Surzhikov; Kerstin Neumann; Andreas Graner; Karl Hammer; Anna Filatenko; et al. (Theoretical and Applied Genetics, 2022)
Key message We present a comprehensive survey of cytogenetic and genomic diversity of the GGA t A t genepool of wheat, thereby unlocking these plant genetic resources for wheat improvement. Abstract Wheat yields are stagnating around the world and new sources of genes for resistance or tolerances to abiotic traits are required. In this context, the tetraploid wheat wild relatives are among the key candidates for wheat improvement. Despite its potential huge value for wheat breeding, the tetraploid GGA t A t genepool is largely neglected. Understanding the population structure, native distribution range, intraspecific variation of the entire tetraploid GGA t A t genepool and its domestication history would further its use for wheat improvement. The paper provides the first comprehensive survey of genomic and cytogenetic diversity sampling the full breadth and depth of the tetraploid GGA t A t genepool. According to the results obtained, the extant GGA t A t genepool consists of three distinct lineages. We provide detailed insights into the cytogenetic composition of GGA t A t wheats, revealed group- and population-specific markers and show that chromosomal rearrangements play an important role in intraspecific diversity of T. araraticum . The origin and domestication history of the GGA t A t lineages is discussed in the context of state-of-the-art archaeobotanical finds. We shed new light on the complex evolutionary history of the GGA t A t wheat genepool and provide the basis for an increased use of the GGA t A t wheat genepool for wheat improvement. The findings have implications for our understanding of the origins of agriculture in southwest Asia.

Correction to: Genetic diversity, distribution and domestication history of the neglected GGAtAt genepool of wheat - Ekaterina D. Badaeva; Fedor A. Konovalov; Helmut Knüpffer; Agostino Fricano; Alevtina S. Ruban; Zakaria Kehel; Svyatoslav A. Zoshchuk; Sergei A. Surzhikov; Kerstin Neumann; Andreas Graner; Karl Hammer; Anna Filatenko; et al. (Theoretical and Applied Genetics, 2021)

Taxonomic remarks on Triticum L. and ×Triticosecale Wittm. - Karl Hammer; Anna A. Filatenko; Klaus Pistrick (Genetic Resources and Crop Evolution, 2011)

Six new botanical varieties of Triticum from Oman - Anna A. Filatenko; Karl Hammer; Sulaiman Al Khanjari; Andreas Buerkert (Genetic Resources and Crop Evolution, 2010)

A new gross morphological variation in the genus Triticum L. - Anna A. Filatenko; Karl Hammer (Genetic Resources and Crop Evolution, 2007)